Users or traffickers? Legal ambiguities in Indonesia’s narcotics law and their role in prison overcrowding - Nevey Varida Ariani; Yusramizza Md Isa; Yuhanif Yusof; Amirudin (Jurnal Hukum Novelty, 2026)
Introduction to the Problem: Drug law enforcement in Indonesia is undermined by persistent legal ambiguities, particularly in distinguishing between drug users and traffickers. This uncertainty erodes legal certainty, generates judicial inconsistencies, and contributes directly to chronic prison overcrowding. Purpose/Study Objectives: This study analyses inconsistencies in Law No. 35 of 2009 regarding the classification of drug users and traffickers and their impact on sentencing disparities and overcrowding. Design/Methodology/Approach: A juridical-empirical method was employed, combining normative legal analysis with qualitative data from semi-structured interviews with four judges and ten inmates in East Java. Findings: Empirical evidence shows that users are frequently misclassified as traffickers through the routine use of Article 112, even for small personal-use quantities suited to Article 127. Despite SEMA No. 4/2010 and No. 3/2015, their clarifying impact has been limited. This misclassification restricts access to rehabilitation, fuels overcrowding, and produces sentencing disparities, thereby weakening substantive justice. This is the first empirically grounded study linking statutory ambiguity with systemic overcrowding in Indonesia. By connecting doctrinal ambiguity with systemic over-incarceration, the study recommends statutory harmonisation, expansion of rehabilitation alternatives, and selective decriminalisation consistent with human rights. Paper type: Research Article